Thermal Stability and Tribological Performance of DLC-Si–O Films. (25th October 2011) - Moolsradoo, Nutthanun; Abe, Shinya; Watanabe, Shuichi
Abstract : The thermal stability and tribological performance of silicon- and oxygen-incorporated diamond-like carbon films were investigated. The DLC-Si-O films were deposited using plasma-based ion implantation (PBII) method. The deposited films were annealed at 400°C, 600°C, and 750°C for 1 hour in vacuum, in argon, and in air atmospheres. Film properties were investigated using the Fourier transforms infrared spectroscopy, Raman spectroscopy, energy dispersive X-ray spectroscopy, and a ball-on-disk friction tester. The structures of the DLC-Si-O films with a low Si content (≤ 25 at.%Si, ≤ 1 at.%O) and high Si content (> 25 at.%Si, > 1 at.%O) were not affected by the thermal annealing in vacuum at 400°C and 600°C, respectively, while they were affected by thermal annealing in argon and in air at 400°C. Film with 34 at.%Si and 9 at.%O after annealing demonstrated almost constant atomic contents until annealing at 600°C in vacuum. The friction coefficient of DLC-Si–O films with 34 at.%Si and 9 at.%O was shown to be relatively stable, with a friction coefficient of 0.04 before annealing and 0.05 after annealing at 600°C in vacuum. Moreover, the low friction coefficient of film annealed at 600°C in vacuum with 34 at.%Si and 9 at.%O was corresponded with low wear rate of 1.85× 10 −7  mm 3 /Nm.